2011
DOI: 10.1371/journal.pone.0016414
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation with Recombinant PfEMP1 Domains Elicits Functional Rosette-Inhibiting and Phagocytosis-Inducing Antibodies to Plasmodium falciparum

Abstract: BackgroundRosetting is a Plasmodium falciparum virulence factor implicated in the pathogenesis of life-threatening malaria. Rosetting occurs when parasite–derived P. falciparum Erythrocyte Membrane Protein One (PfEMP1) on the surface of infected erythrocytes binds to human receptors on uninfected erythrocytes. PfEMP1 is a possible target for a vaccine to induce antibodies to inhibit rosetting and prevent severe malaria.Methodology/FindingsWe examined the vaccine potential of the six extracellular domains of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 63 publications
7
83
2
Order By: Relevance
“…The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51). Previously, the only known binding phenotype for group A PfEMP1 variants was rosetting (20)(21)(22)(23), with two group A domain cassettes (DC11 and DC16) being linked to rosette formation (24). DC16 was not associated with severe malaria in the study by Lavstsen et al (44) and DC11 was not tested.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51). Previously, the only known binding phenotype for group A PfEMP1 variants was rosetting (20)(21)(22)(23), with two group A domain cassettes (DC11 and DC16) being linked to rosette formation (24). DC16 was not associated with severe malaria in the study by Lavstsen et al (44) and DC11 was not tested.…”
Section: Discussionmentioning
confidence: 95%
“…IFA with rabbit preimmune and immune sera and live IEs were carried out as described (23). For each antigen, the rabbit serum giving the brightest IFA signal with the lowest background was chosen for purification of total IgG.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations